Data-Driven Management : Utilisation of Big Data in HR Decision Making in the Digital Age - Ivan Widjaja; Budi Eko Soetjipto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of digital technology has encouraged organisations to adopt big data analytics in human resource management (HRM), but there are still challenges in leveraging it for effective decision-making. This study aims to investigate the effect of big data utilisation on the quality of HR decision-making and identify the supporting and inhibiting factors for its implementation. A quantitative method with purposive sampling survey was conducted on 100-150 respondents from companies that have implemented big data-based management information systems and HR analytics. Data were analysed using Structural Equation Modeling (SEM) with AMOS software. The results showed that big data analytics significantly improved the quality of HR decision-making, with HR digital competencies and organisational culture as important mediating factors. However, challenges related to cultural resistance and limited expertise were found to affect the effectiveness of implementation. The practical implications of this research emphasise the importance of HR digital capacity building and ethical data governance to support the transformation of HRM into an adaptive strategic function in the digital era. This research also contributes to the development of data-driven management theory with a holistic approach that integrates technical, human, and ethical aspects.